Zusatznutzen Berg? Argumente fur̈ den Konsum von Bergprodukten - Anja Matscher; Markus Schermer (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2009)
– Given the broad range of products in food retailing, actors are increasingly aiming to differentiate their products by promoting certain features as added benefits. This means that any added (emotional) benefit, whichever way it is communicated, becomes significant. In this article we investigate inhowfar the fact that a product originates from a mountain region constitutes such an added benefit for consumers and what arguments support their choice of mountain food products. We present results of four focus groups with participants from Austria (Tyrol) and Germany, analysed by using Convention Theory. Our findings suggest that the origin of a food product in a mountain region does not constitute a singular added benefit but rather the sum of several components associated with a mountain origin, in varying combinations, depending on the specific focus group. The statements gathered in the focus groups may thus provide some indication on how to improve the communication strategy for mountain products.
Keywords: 330; Konsumentenverhalten; Nutzen; Käse; Mineralwasser; Tirol; Österreich; Deutschland